Can computed tomography volumetry of the renal cortex replace MAG3-scintigraphy in all patients for determining split renal function?. Issue 103 (June 2018) - Houbois, Christian; Haneder, Stefan; Merkt, Martin; Morelli, John N.; Schmidt, Matthias; Hellmich, Martin; Mueller, Roman-Ulrich; Wahba, Roger; Maintz, David; Puesken, Michael
Highlights: CT-based RCV is a potential replacement for MAG3-scintigraphy in the determination of split renal function. RCV demonstrates clinically tolerable differences to MAG3-scintigraphy independent of patient eGFR. RCV showed an acceptable but only fair to moderate intra-reader reliability. Abstract: Objectives: The current gold standard for determination of split renal function (SRF) is Tc-99m-mercapto-acetyltriglycin (MAG3) scintigraphy. Initial studies comparing MAG3-scintigraphy and CT-based renal cortex volumetry (RCV) for calculation of SRF have shown similar results in highly selected patient collectives with normal renal function (i.e. living kidney donors). This study aims to compare MAG3-scintigraphy and CT-RCV within a large unselected patient collective including patients with impaired renal function. Materials and methods: For this assessment, 279 datasets (131 men, 148 women; mean age: 54.2 ± 12.9 years, range: 24–84 years) of patients who underwent MAG3-scintigraphy and contrast-enhanced abdominal CT within two weeks were retrospectively analyzed. Two independent readers assessed the CT-RCV in all CT datasets using a semi-automated volumetry tool. The MAG3-scintigraphy and CT-RCV methods were compared, stratified for the eGFR. Statistical analysis included descriptive statistics as well as inter- observer agreement. Results: The absolute mean difference between the percentage contribution of the left and the right kidneys in total MAG3-clearance was 8.6%. Independent of eGFR, an overall sufficient agreement between both methods was established in all patients. A relatively small, tolerable systemic error resulted in an underestimation (max. 2%) of the left renal contribution to overall RCV. Conclusion: The results demonstrate that CT-RCV is a potential clinical replacement for MAG3-scintigraphy for calculation of SRF: CT-RCV demonstrates clinically tolerable differences with MAG3-scintigraphy, independent of patient eGFR. The relative complexity of the RCV method utilized is a potential limitation and may have contributed to the acceptable but only fair to moderate level of intra-reader reliability.